2019
DOI: 10.1038/s41409-019-0690-2
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated gemtuzumab ozogamicin in association with high dose chemotherapy: a bridge to allogeneic stem cell transplantation in refractory and relapsed acute myeloid leukemia

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…Our results were in accordance with those recently published showing a viable option for GO-based chemotherapy as salvage therapy, with similar survival rates and a feasible schedule as a bridge to allogeneic HSCT. 23 Main prognostic factors appeared related to the intensity of prior therapy since a history of prior transplantation was of adverse influence and also related to leukemia cell characteristics such as the genetic profile. Overall, allogeneic HSCT performed after CR achievement following GO therapy remained the major prognostic factor for both DFS and OS.…”
Section: Results Population Characteristicsmentioning
confidence: 99%
“…Our results were in accordance with those recently published showing a viable option for GO-based chemotherapy as salvage therapy, with similar survival rates and a feasible schedule as a bridge to allogeneic HSCT. 23 Main prognostic factors appeared related to the intensity of prior therapy since a history of prior transplantation was of adverse influence and also related to leukemia cell characteristics such as the genetic profile. Overall, allogeneic HSCT performed after CR achievement following GO therapy remained the major prognostic factor for both DFS and OS.…”
Section: Results Population Characteristicsmentioning
confidence: 99%
“… 52 , 53 The fractionated dosage of GO was observed in the phase 2 MyloFrance‐1 trial for the first Relapsed or refractory (R/R) CD33‐positive AML patients; 26% of patients achieved complete remission (CR) with a median relapse‐free survival (RFS) of 11 months and manageable toxicities, which led to FDA approval. 54 Several studies explored the efficacy of GO in combination with chemotherapy as salvage therapy, including the combination of GO and DA therapy (daunorubicin plus cytarabine) (overall response rate [ORR]: 38.8%; CR rate: 22.2%; 2‐year RFS rate: 18.5%; 2‐year overall survival [OS] rate: 26%), 55 the combination of GO and MYLODAM schema (cytarabine and mitoxantrone) (ORR: 67%; 2‐year RFS rate: 36%; 2‐year OS rate: 54%), 56 the combination of GO and high‐dose cytarabine, mitoxantrone, and all‐trans retinoic acid (ATRA) (CR/CR with incomplete hematologic recovery [CRi] rate: 51%; ORR: 61.5%; 4‐year OS rate: 32%), 57 as well as the combination of GO and decitabine (CR/CRi rate: 18%; median OS: 3.5 months). 58 Moreover, two phase 1/2 trials showed the enhanced efficacy of hypomethylating agent therapy in addition to GO through epigenetic effects in R/R AML patients (NCT00766116 trial, GO, plus azacytidine; CR/CRi rate: 24%; NCT00895934 trial, GO, azacytidine, plus vorinostat; CR/CRi rate: 41.9%; median OS: 224.5 days).…”
Section: Clinical Application Of Adcsmentioning
confidence: 99%
“…Incidences of nonrelapse mortality, grade II-IV acute graft-versus-host disease (GVHD) and chronic GVHD were 16%, 40%, and 45%, respectively [82].…”
Section: Antibody-drug Conjugate (Adc)mentioning
confidence: 99%
“…In a French study of 58 primary refractory or relapsed acute myeloid leukemia (AML) patients with a median age at salvage of 56 years, the combination of fractionated GO with cytarabine and mitoxantrone achieved an ORR of 67%, and the leukemia-free survival (LFS) and OS at 2 years was 36% and 54%, respectively. Incidences of nonrelapse mortality, grade II-IV acute graft-versus-host disease (GVHD) and chronic GVHD were 16%, 40%, and 45%, respectively [ 84 ].…”
Section: Targeted Cell Surface Antigen In R/r Amlmentioning
confidence: 99%